Psychometric Properties of the Perinatal Anxiety Screening Scale Administered to Italian Women in the Perinatal Period - Koukopoulos, Alexia; Mazza, Cristina; De Chiara, Lavinia; Sani, Gabriele; Simonetti, Alessio; Kotzalidis, Georgios D.; Armani, Giulia; Callovini, Gemma; Bonito, Marco; Parmigiani, Giovanna; Ferracuti, Stefano; Somerville, Susanne; et al. (Frontiers in Psychiatry, 2021)
Literature stressed the importance of using valid, reliable measures to assess anxiety in the perinatal period, like the self-rated Perinatal Anxiety Screening Scale (PASS). We aimed to examine the psychometric properties of the Italian PASS version in a sample of Italian women undergoing mental health screening during their third trimester of pregnancy and its diagnostic accuracy in a control perinatal sample of psychiatric outpatients. Sample comprised 289 women aged 33.17±5.08, range 19-46 years, undergoing fetal monitoring during their third trimester of pregnancy, with 49 of them retested six months postpartum. Controls were 60 antenatal or postnatal psychiatric outpatients aged 35.71±5.02, range 22-50 years. Groups were assessed through identical self- and clinician-rating scales. Confirmatory Factor Analysis (CFA), Principal Component Analysis (PCA), Pearson’s correlations and receiver operating characteristic were conducted for PASS. PCA and CPA confirmed four-factor structure with slight differences from the original version. Construct validity and test-retest reliability were supported. Cutoff was 26. The PASS correlated with principal anxiety scales. Despite small sample size, findings confirm reliability and validity of the Italian PASS version in assessing anxiety symptoms in the perinatal period. Its incorporation in perinatal care will improve future mother and child psychological health.